Low-voltage CMOS triode transconductorwith wide-range and linear tunability - Zeki, A. (Institution of Engineering and Technology (IET), 1999)
A triode transconductor is proposed which has a transconductance that is linearly tuneable over a wide range (more than two decades) when the circuit is operated from a 3.3 V power supply. The THD is <1% within the whole linear tuning range, for a 10 MHz differential input signal of 1 V/sub peak/.